Pengaruh Struktur Modal, Ukuran Perusahaan, dan Likuiditas Terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Juliatri, Baiq Zilvia; Wijayanti, Inung (Neolectura, 2024)
The research aims to examine the influence of capital structure, company size and liquidity on company value and profitability as intervening variables in manufacturing companies listed on the Indonesia Stock Exchange in the 2018-2022 period. A population of 54 companies was sampled using a purposive sampling technique, a sample of 26 companies. The results of the partial analysis of capital structure have no effect on profitability with a prob value of 0.8319, company size has an effect on profitability with a prob value of 0.0256, liquidity has no effect on profitability, a prob value of 0.5181 capital structure has no effect on company value with a prob value of 0.2165, company size has an effect on company value with a prob value of 0.000 liquidity has no effect on company value with a prob value of 0.3862 profitability has an effect on company value with a prob value of 0.000. Simultaneously, capital structure, company size, liquidity have no effect on profitability with a prob value of 0.153343, while capital structure, company size, liquidity and profitability have an effect on company value with a prob value of 0.0000.